The broad-spectrum rice blast resistance (R) gene Pita2 encodes a novel R protein unique from Pita - Meng, Xiuli; Xiao, Gui; Telebanco-Yanoria, Mary Jeanie; Siazon, Paolo Miguel; Padilla, Jonas; Opulencia, Rina; Bigirimana, Joseph; Habarugira, Georges; Wu, Jun; Li, Mingyang; Wang, Baohua; Lu, Guodong; et al. (Springer, 2020)
Rice blast is generally considered the most devastating rice disease worldwide. The development of resistant varieties has been proven to be the most economical strategy to control the disease. A cluster of resistant (R) genes on rice chromosome 12 including Pita, Pita2 and Ptr has been studies for decades. However, the relationship between these R genes has not been well established. Results In this study, we compared the resistance spectra controlled by Pita2 and Pita by testing their monogenic lines (MLs) in four hotspots found in the Philippines and Burundi from 2014 to 2018. The reaction patterns were distinct in two countries and that Pita2-mediated field resistance was relatively prevalent. Pathogenicity tests using 328 single-spore isolates in greenhouse further verified that IRBLta2-Re for Pita2 conferred a relatively broader spectrum resistance than those of Pita. Rough and fine mapping of Pita2 were conducted using F2 and F3 populations derived from IRBLta2-Re [CO] and CO 39 consisting of 4344 progeny to delimit Pita2 in a genomic interval flanked by two markers 12 g18530 and 12 g18920 proximal to the centromere of chromosome 12. Alignment of the markers to the genomic sequence of IR64, which harbors Pita2 verified by genetic analysis, approximately delimited the candidate gene(s) within 313-kb genomic fragment. The two Pita2 suppressive mutants that contain mutations within Pita2 were verified and identified. Comparative sequence analysis in these two mutants further identified that each individual allele contains a single nucleotide substitution at a different position resulting in nonsense and missense mutations in the protein product of LOC_Os12g18729. On the contrary, no sequence mutation was detected in other candidate genes, indicating that mutations in LOC_Os12g18729 were responsible for the loss of function of Pita2. Pita2 encodes a novel R protein unique from Pita, which is exactly identical to the previously cloned Ptr. Moreover, based on the resistance gene analysis of rice varieties and mutants containing Pita, it was found that Pita2 rather than Pita was responsible for the specificity to some differential isolates with AvrPita. The diagnosis and survey of Pita2 in IRRI released varieties showed relatively low frequency, implying a high value of its application for breeding resistant varieties against rice blast via marker assisted selection. Conclusion Our study clarified the relationship between Pita, Pita2 and Ptr. Pita2 is identical to Ptr and distinct from Pita in both sequence and chromosomal location although Pita2 and Pita are genetically linked to each other. The loss of function of Pita2 but not Pita eliminate the specificity to some AvrPita containing isolates, however, the mechanism underlying the recognition between Pita2/Pita and AvrPita remains elusive.